Emergency Department Management of Obstetric Complications - Borhart, Joelle (Springer International Publishing : Imprint: Springer, 2017)
Obstetrical emergencies can be among the most stressful events an emergency physician will face in their entire career. The purpose of this book is to provide an evidence-based, practical approach to the wide spectrum of obstetric complications an emergency physician must be prepared to manage throughout all trimesters pregnancy as well as postpartum, including complications of assisted reproductive technology, bleeding, precipitous delivery and preterm labor. Clinical pearls and pitfalls are highlighted throughout. The approach to the pregnant patient with trauma, non-pregnancy-related abdominal pain, or in cardiac arrest is discussed. Updates in the classification and management of the hypertensive disorders of pregnancy are presented. Recent controversies surrounding the use of anti-emetics for first trimester nausea and vomiting and the use of a beta-hCG discriminatory zone for the evaluation of pregnancy of unknown location are also addressed. Obstetrical support services vary widely between different facilities, and Emergency Department Management of Obstetric Complications is written for emergency clinicians in all practice settings. This book provides useful information for daily practice as well as preparation for rarely encountered and potentially life-threatening events.